Transparent Conductive Film
Patent Information
- Application Number
- JP2019115612
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-06-21
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2039-06-21
Smart Images

Figure 0007638058000005 
Figure 0007638058000001 
Figure 0007638058000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a transparent conductive film, and more particularly to a transparent conductive film suitable for optical applications. [Background technology]
[0002] Transparent conductive films in which a transparent conductive layer made of indium tin oxide (ITO) is formed into a desired electrode pattern have been used for optical applications such as touch panels.
[0003] Such a transparent conductive film usually comprises a substrate and a transparent conductive layer in that order.
[0004] Conventionally, it has been known to use a relatively thick glass substrate as the substrate.
[0005] However, when a relatively thick glass substrate is used as the substrate, flexibility is reduced. Therefore, from the viewpoint of improving flexibility, the use of a polymer film as the substrate has been considered.
[0006] On the other hand, by first increasing the temperature of the substrate and then forming the film, it is possible to crystallize the ITO (also called "as-deposited crystallization") at the same time as the film is formed. It is known that such as-deposited crystallization can reduce the surface resistance of the transparent electrode layer compared to forming the film in an amorphous state and then crystallizing it. However, in such a case, since the film is formed by raising the temperature of the substrate to a high temperature, a polymer film cannot be used from the viewpoint of the heat resistance of the polymer film.
[0007] Therefore, from the viewpoint of improving flexibility and lowering surface resistance, the use of thin glass as the substrate has been considered.
[0008] For example, a transparent laminated substrate including an ultrathin transparent glass substrate and a transparent conductive oxide layer has been proposed (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP2017-106124A Summary of the Invention [Problem to be solved by the invention]
[0010] However, compared with polymer films, thin glass has low strength against bending stress, so that when thin glass is used as a substrate as in Patent Document 1, there is a problem in that bending resistance is reduced.
[0011] In particular, thin glass is required to have even greater bending resistance than polymer films, since it may be broken by bending.
[0012] The present invention provides a transparent conductive film having excellent bending resistance. [Means for solving the problem]
[0013] The present invention [1] is a transparent conductive film comprising, in order, a glass substrate and a transparent conductive layer, the thickness of the glass substrate being 150 μm or less, the transparent conductive layer being crystalline, and the residual stress of the transparent conductive layer being less than −100 MPa or exceeding 100 MPa.
[0014] The present invention [2] includes the transparent conductive film according to claim 1, in which the surface resistance of the transparent conductive layer is 30 Ω / □ or less.
[0015] The present invention [3] includes the transparent conductive film according to the above [1] or [2], in which the transparent conductive layer contains a metal oxide.
[0016] The present invention [4] includes the transparent conductive film according to the above [3], characterized in that the metal oxide is an indium tin composite oxide. Effect of the Invention
[0017] The transparent conductive film of the present invention includes a glass substrate and a transparent conductive layer in this order, and the thickness of the glass substrate is 150 μm or less, and therefore has excellent flexibility.
[0018] In addition, in this transparent conductive film, the transparent conductive layer is crystalline. Therefore, the surface resistance value can be reduced. In addition, in this transparent conductive film, the residual stress of the transparent conductive layer is less than -100 MPa or exceeds 100 MPa. This allows the transparent conductive layer to relax bending stress, resulting in excellent bending resistance. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 shows a cross-sectional view of one embodiment of the transparent conductive film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] One embodiment of the transparent conductive film of the present invention will be described with reference to FIG.
[0021] In Fig. 1, the up-down direction of the paper is the up-down direction (thickness direction), the upper side of the paper is the upper side (one side in the thickness direction), and the lower side of the paper is the lower side (the other side in the thickness direction). The left-right direction and the depth direction of the paper are surface directions perpendicular to the up-down direction. Specifically, they follow the directional arrows in each figure.
[0022] 1. Transparent conductive film The transparent conductive film 1 has a film shape (including a sheet shape) with a predetermined thickness, extends in a plane direction perpendicular to the thickness direction, and has a flat upper surface and a flat lower surface. The transparent conductive film 1 is, for example, a part of a touch panel substrate or an electromagnetic shield provided in an image display device, that is, it is not an image display device. In other words, the transparent conductive film 1 is a part for producing an image display device or the like, does not include an image display element such as an OLED module, is distributed as a part alone, and is an industrially applicable device.
[0023] 1, the transparent conductive film 1 includes, in this order, a glass substrate 2 and a transparent conductive layer 3. More specifically, the transparent conductive film 1 includes the glass substrate 2 and the transparent conductive layer 3 disposed on the upper surface (one surface in the thickness direction) of the glass substrate 2.
[0024] The transparent conductive film 1 has a thickness of, for example, 200 μm or less, preferably 150 μm or less, and for example, 20 μm or more, preferably 30 μm or more.
[0025] 2. Glass substrate The glass substrate 2 is a transparent substrate for ensuring the mechanical strength of the transparent conductive film 1. In other words, the glass substrate 2 supports the transparent conductive layer 3.
[0026] The glass substrate 2 has a film shape and is disposed over the entire lower surface of the transparent conductive layer 3 so as to be in contact with the lower surface of the transparent conductive layer 3.
[0027] The glass substrate 2 is made of flexible, transparent glass.
[0028] Examples of the glass include non-alkali glass, soda glass, borosilicate glass, and aluminosilicate glass.
[0029] The thickness of the glass substrate 2 is 150 μm or less, preferably 120 μm or less, more preferably 100 μm or less. Also, for example, it is 10 μm or more, preferably 50 μm or more. When the thickness of the glass substrate 2 is equal to or less than the above upper limit, the glass substrate 2 has excellent flexibility. When the thickness of the glass substrate 2 is equal to or more than the above lower limit, the glass substrate 2 has excellent mechanical strength and can be prevented from being damaged during transportation.
[0030] The thickness of the glass substrate 2 can be measured using a dial gauge (manufactured by PEACOCK, "DG-205").
[0031] The total light transmittance (JIS K 7375-2008) of the glass substrate 2 is, for example, 80% or more, or preferably 85% or more.
[0032] 3. Transparent conductive layer The transparent conductive layer 3 is a crystalline, transparent layer that exhibits excellent electrical conductivity.
[0033] The transparent conductive layer 3 has a film shape. The transparent conductive layer 3 is disposed on the entire upper surface of the glass substrate 2 so as to be in contact with the upper surface of the glass substrate 2.
[0034] Examples of materials for the transparent conductive layer 3 include metal oxides containing at least one metal selected from the group consisting of In, Sn, Zn, Ga, Sb, Ti, Si, Zr, Mg, Al, Au, Ag, Cu, Pd, and W. If necessary, the metal oxides may be doped with metal atoms shown in the above group.
[0035] Specific examples of the transparent conductive layer 3 include indium-containing oxides such as indium tin oxide (ITO) and antimony-containing oxides such as antimony tin oxide (ATO), and preferably indium-containing oxides, and more preferably ITO.
[0036] When ITO is used as the material of the transparent conductive layer 3, the tin oxide (SnO2) content is, for example, 0.5 mass% or more, preferably 3 mass% or more, and for example, 15 mass% or less, preferably 13 mass% or less, based on the total amount of tin oxide and indium oxide (In2O3). If the tin oxide content is equal to or more than the above lower limit, the durability of the ITO layer can be further improved. If the tin oxide content is equal to or less than the above upper limit, the crystallization of the ITO layer can be facilitated, and the stability of the transparency and resistivity can be improved.
[0037] In this specification, "ITO" refers to a composite oxide containing at least indium (In) and tin (Sn), and may contain additional components other than these. Examples of additional components include metal elements other than In and Sn, such as Zn, Ga, Sb, Ti, Si, Zr, Mg, Al, Au, Ag, Cu, Pd, W, Fe, Pb, Ni, Nb, Cr, and Ga.
[0038] The transparent conductive layer 3 is crystalline.
[0039] If the transparent conductive layer 3 is crystalline, the surface resistivity, which will be described later, can be reduced.
[0040] The crystallinity of the transparent conductive layer 3 can be determined, for example, by immersing the transparent conductive film 1 in hydrochloric acid (20°C, concentration 5% by mass) for 15 minutes, followed by rinsing with water and drying, and then measuring the resistance between terminals about 15 mm from the surface on the side of the transparent conductive layer 3. If the resistance between terminals over 15 mm in the transparent conductive film 1 after the immersion, rinsing with water and drying is 10 kΩ or less, the transparent conductive layer is crystalline, whereas if the resistance exceeds 10 kΩ, the transparent conductive layer 3 is amorphous.
[0041] The resistivity of the upper surface of the transparent conductive layer 3 is, for example, 2.0×10 -4 Ω cm or less, preferably 1.8×10 -4 Ω cm or less, more preferably 1.5×10 -4 Ω·cm or less, more preferably 1.2×10 -4Ω cm or less, for example, 1.0×10 -4 The resistivity is Ω·cm or more. The resistivity can be measured by the four-terminal method in accordance with JIS K7194.
[0042] The surface resistivity of the upper surface of the transparent conductive layer 3 is, for example, 30 Ω / □ or less, preferably 15 Ω / □ or less, more preferably 13 Ω / □ or less, and even more preferably 12 Ω / □ or less, and for example, 1 Ω / □ or more, preferably 10 Ω / □ or more. The surface resistivity can be measured by a four-terminal method in accordance with JIS K7194.
[0043] If the surface resistivity is equal to or less than the above upper limit, the transparent conductive film 1 can be suitably used for large touch panels and the like.
[0044] The residual stress of the transparent conductive layer 3 is less than -100 MPa, preferably -200 MPa or less, more preferably -300 MPa or less, even more preferably -400 MPa or less, and for example, -1000 MPa or more, preferably -800 Pa or more from the viewpoint of reducing the resistivity.
[0045] Furthermore, the residual stress of the transparent conductive layer 3 exceeds 100 MPa, and is preferably 300 MPa or more, and is, for example, 1000 MPa or less.
[0046] Here, negative residual stress means residual stress in the compression direction, and positive residual stress means residual stress in the elongation direction.
[0047] When the negative residual stress of the transparent conductive layer 3 is less than the above upper limit, the residual stress of the transparent conductive layer 3 becomes large, and the bending resistance is improved.
[0048] On the other hand, if the negative residual stress of the transparent conductive layer 3 is equal to or greater than the upper limit, the residual stress of the transparent conductive layer 3 becomes small, and the bending resistance decreases.
[0049] Furthermore, if the positive residual stress of the transparent conductive layer 3 exceeds the above lower limit, the residual stress of the transparent conductive layer 3 increases, improving the bending resistance.
[0050] On the other hand, if the negative residual stress of the transparent conductive layer 3 is equal to or lower than the above lower limit, the residual stress of the transparent conductive layer 3 becomes small, and the bending resistance decreases.
[0051] The residual stress can be determined by X-ray diffraction, as will be described in detail in the examples below.
[0052] Specifically, the residual stress can be determined in accordance with the residual stress measurement method described in JP 2017-106124 A.
[0053] Furthermore, the residual stress can be adjusted to the above-mentioned range by adjusting the amount of reactive gas introduced, the film formation pressure, and the substrate temperature, all of which will be described in detail later.
[0054] The transparent conductive layer 3 has a thickness of, for example, 15 nm or more, preferably 30 nm or more, more preferably 100 nm or more, and for example, 300 nm or less, preferably 250 nm or less, more preferably 150 nm or less. The thickness of the transparent conductive layer 3 can be measured by observing a cross section of the transparent conductive film 1 using, for example, a transmission electron microscope. 4. Manufacturing method of transparent conductive film To manufacture the transparent conductive film 1, for example, in a roll-to-roll process, a transparent conductive layer 3 is provided on the upper surface of a glass substrate 2. Specifically, while the long glass substrate 2 is fed from a feed roll and transported downstream in the transport direction, the transparent conductive layer 3 is provided on the upper surface of the glass substrate 2, and the conductive film 1 is taken up by a take-up roll. This will be described in detail below.
[0055] First, a long glass base material 2 wound around a delivery roll is prepared, and the glass base material 2 is transported so as to be wound around a take-up roll.
[0056] The conveying speed is, for example, 0.1 m / min or more, preferably 0.2 m / min or more, and for example, 1.0 m / min or less, preferably 0.5 m / min or less.
[0057] Thereafter, if necessary, etching treatments or undercoating treatments such as sputtering, corona discharge, flame, ultraviolet irradiation, electron beam irradiation, chemical conversion, and oxidation may be performed on the surface of the glass substrate 2 from the viewpoint of adhesion between the glass substrate 2 and the transparent conductive layer 3. In addition, the glass substrate 2 may be cleaned by solvent cleaning, ultrasonic cleaning, or the like to remove dust.
[0058] Next, a transparent conductive layer 3 is provided on the upper surface of the glass substrate 2. For example, the transparent conductive layer 3 is formed on the upper surface of the glass substrate 2 by a dry method.
[0059] Examples of the dry method include vacuum deposition, sputtering, and ion plating. Sputtering is preferred. This method can form a thin transparent conductive layer 3 with a uniform thickness.
[0060] In the sputtering method, a target and an adherend (glass substrate 2) are placed facing each other in a vacuum chamber, and gas is supplied while a voltage is applied from a power source to accelerate the gas ions and irradiate the target, ejecting the target material from the target surface and depositing the target material on the adherend surface.
[0061] Examples of the sputtering method include a dipole sputtering method, an ECR (electron cyclotron resonance) sputtering method, a magnetron sputtering method, an ion beam sputtering method, etc. Preferably, the magnetron sputtering method is used.
[0062] When the sputtering method is employed, examples of the target material include the above-mentioned metal oxides constituting the transparent conductive layer 3, and preferably ITO. The tin oxide concentration of ITO is, from the viewpoints of durability, crystallization, etc. of the ITO layer, for example, 0.5 mass % or more, preferably 3 mass % or more, and for example, 15 mass % or less, preferably 13 mass % or less.
[0063] The gas may be, for example, an inert gas such as Ar. If necessary, a reactive gas such as oxygen gas may be used in combination.
[0064] The ratio of the reactive gas introduced to the inert gas (hereinafter referred to as the reactive gas introduction amount) is, for example, 0.1 vol.% or more, preferably 1 vol.% or more, and for example, 10 vol.% or less, preferably 7 vol.% or less, and more preferably 5 vol.% or less.
[0065] The pressure during sputtering (hereinafter referred to as film formation pressure) is, for example, 1 Pa or less, or preferably 0.5 Pa or less, and for example, 0.1 Pa or more, or preferably 0.2 Pa or more.
[0066] The power source may be, for example, a DC power source, an AC power source, an MF power source, or an RF power source, or may be a combination of these.
[0067] In this sputtering, the glass substrate 2 is heated to a high temperature beforehand. This places the particles that form the transparent conductive layer 3 on the surface of the glass substrate 2 in a high energy state, allowing them to crystallize (as-deposited crystallization) simultaneously with the film formation by sputtering.
[0068] The heating temperature of the glass substrate 2 (hereinafter referred to as substrate temperature) is, for example, 250° C. or more, preferably 350° C. or more, and for example, 600° C. or less, preferably 550° C. or less.
[0069] The heating time of the glass substrate 2 is, for example, 10 seconds or more, preferably 20 seconds or more, and for example, 120 seconds or less, preferably 60 seconds or less.
[0070] From the viewpoint of adjusting the residual stress of the transparent conductive layer 3 to the above-mentioned predetermined range, the amount of reactive gas introduced, the film formation pressure, and the substrate temperature are preferably adjusted to the above-mentioned predetermined ranges.
[0071] Specifically, when the substrate temperature is 250° C. or more and less than 350° C., the amount of reactive gas introduced is, for example, 1 vol. % or more and 3 vol. % or less, and the film formation pressure is, for example, 0.1 Pa or more and 0.5 Pa or less.
[0072] When the substrate temperature is 350° C. or higher and 550° C. or lower, the amount of reactive gas introduced is, for example, 2.5 vol. % or higher and less than 3.5 vol. %, and the deposition pressure is, for example, 0.2 Pa or higher and 0.5 Pa or lower. When the substrate temperature is 350° C. or higher and 550° C. or lower, the amount of reactive gas introduced is, for example, 5 vol. % or higher and 7 vol. % or lower, and the deposition pressure is, for example, 0.1 Pa or higher and 0.2 Pa or lower.
[0073] This makes it possible to adjust the residual stress of the transparent conductive layer 3 to fall within the predetermined range.
[0074] After the transparent conductive layer 3 is heated, the transparent conductive layer 3 is cooled.
[0075] As a result, the transparent conductive layer 3 is formed on the upper surface of the glass substrate 2, and a transparent conductive film 1 including the glass substrate 2 and the transparent conductive layer 3 in this order is obtained.
[0076] The thickness of the obtained transparent conductive film 1 is, for example, 2 μm or more, preferably 20 μm or more, and for example, 100 μm or less, preferably 50 μm or less. 5. Effects The transparent conductive film 1 includes a glass substrate 2 and a transparent conductive layer 3 in this order, and the thickness of the glass substrate 2 is 150 μm or less, and therefore has excellent flexibility.
[0077] Furthermore, in the transparent conductive film 1, the transparent conductive layer 3 is crystalline, which allows the surface resistance value to be reduced.
[0078] In the transparent conductive film 1, the residual stress of the transparent conductive layer 3 is less than −100 MPa or exceeds 100 MPa.
[0079] Therefore, even if bending stress is applied to the transparent conductive film 1, the stress can be alleviated by the transparent conductive layer 3. As a result, the transparent conductive film 1 has excellent bending resistance. 6. Variations In the above description, the transparent conductive film 1 is composed of the glass substrate 2 and the transparent conductive layer 3, but an intermediate layer can be interposed between the glass substrate 2 and the transparent conductive layer 3.
[0080] The intermediate layer may be a hard coat layer.
[0081] The hard coat layer is a protective layer for preventing scratches from occurring on the glass substrate 2 during production of the transparent conductive film 1. In addition, the hard coat layer is an anti-scratch layer for preventing scratches from occurring on the transparent conductive layer 3 when the transparent conductive film 1 is laminated.
[0082] The hard coat layer is formed, for example, from a hard coat composition.
[0083] The hard coat composition contains a resin component.
[0084] Examples of the resin component include a curable resin and a thermoplastic resin (eg, a polyolefin resin).
[0085] The hardcoat composition can also contain particles.
[0086] Examples of the particles include organic particles such as crosslinked acrylic particles, and inorganic particles such as silica particles.
[0087] From the viewpoint of scratch resistance, the thickness of the hard coat layer is, for example, 0.1 μm or more, preferably 0.5 μm or more, and, for example, 10 μm or less, preferably 3 μm or less. The thickness of the hard coat layer can be calculated based on the wavelength of the interference spectrum observed using, for example, an instantaneous multi-photometer system (for example, "MCPD2000" manufactured by Otsuka Electronics Co., Ltd.).
[0088] Moreover, an example of the intermediate layer is an optical adjustment layer.
[0089] The optical adjustment layer is a layer that adjusts the optical properties (e.g., refractive index) of the transparent conductive film 1 in order to suppress visibility of the pattern of the transparent conductive layer 3 and suppress reflection at interfaces within the transparent conductive film 1 while ensuring excellent transparency of the transparent conductive film 1.
[0090] The optical adjustment layer is formed, for example, from an optical adjustment composition.
[0091] The optical adjusting composition contains the above-mentioned resin component and the above-mentioned particles.
[0092] The thickness of the optical adjustment layer is, for example, 5 nm or more, preferably 10 nm or more, and, for example, 200 nm or less, preferably 100 nm or less. The thickness of the optical adjustment layer can be calculated based on the wavelength of the interference spectrum observed using, for example, an instantaneous multi-photometer system.
[0093] In other words, the transparent conductive film 1 can have a hard coat layer or an optical adjustment layer interposed between the glass substrate 2 and the transparent conductive layer 3, and the transparent conductive film 1 can also have a hard coat layer and an optical adjustment layer interposed between the glass substrate 2 and the transparent conductive layer 3.
[0094] Preferably, the transparent conductive film 1 has an optical adjustment layer interposed between the glass substrate 2 and the transparent conductive layer 3, and more preferably, the transparent conductive film 1 has neither a hard coat layer nor an optical adjustment layer interposed between the glass substrate 2 and the transparent conductive layer 3, i.e., the transparent conductive film 1 is composed of the glass substrate 2 and the transparent conductive layer 3.
[0095] In detail, the transparent conductive film 1 uses a glass substrate 2 as the substrate, and therefore has excellent adhesion and transparency, compared to a case where a polymer film is used as the substrate, even without an intermediate layer (particularly, a hard coat layer) being interposed between the glass substrate 2 and the transparent conductive layer 3. EXAMPLES
[0096] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the examples and comparative examples. The specific numerical values of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention". 1. Manufacturing of transparent conductive film Example 1 As the glass substrate, a long transparent glass substrate (thickness: 50 μm, manufactured by Nippon Electric Glass Co., Ltd., "G-Leaf") wound in a roll shape was prepared.
[0097] The transparent glass substrate was set on a delivery roll, sent out at a conveying speed of 0.27 m / min, passed through a sputtering device (target section), and wound around a take-up roll. An ITO layer (transparent conductive layer) having a thickness of 130 nm was formed on the upper surface of the glass substrate by DC sputtering. Sputtering was performed under a vacuum atmosphere of 0.13 Pa (film formation pressure) with 98% argon gas and 2% oxygen gas (i.e., oxygen gas introduction amount 2% by volume). The discharge output was 3 kW. As the target, a sintered body of 87.5% by mass of indium oxide and 12.5% by mass of tin oxide was used. In addition, before sputtering, an infrared heater (heating section) was operated in the sputtering device, the heater temperature (substrate temperature) was set to 500° C., and the glass substrate was heated for 25 seconds.
[0098] In this way, a transparent conductive film having a glass substrate and an ITO layer and wound into a roll was produced.
[0099] Examples 2 to 5 and Comparative Examples 1 to 4 A transparent conductive film was produced in the same manner as in Example 1, except that the substrate temperature, film formation pressure, and oxygen gas introduction amount were changed according to Table 1. 2. Evaluation 1)Surface resistivity The surface resistivity of the ITO layer of each of the examples and comparative examples was measured by a four-terminal method in accordance with JIS K7194. The results are shown in Table 1. 2) Specific resistance The resistivity of the ITO layer of each of the examples and comparative examples was measured by a four-terminal method in accordance with JIS K7194. The results are shown in Table 1. 3) Residual stress The residual stress in the ITO layer of each of the examples and comparative examples was indirectly determined from the crystal lattice distortion of the ITO film by X-ray scattering.
[0100] Specifically, first, the diffraction intensity was measured at intervals of 0.04° in the measurement scattering angle range 2θ=59 to 62° using a powder X-ray diffractometer manufactured by Rigaku Corp. The integration time (exposure time) at each measurement angle was 100 seconds.
[0101] The crystal lattice spacing d of the ITO film was calculated from the peak angle 2θ of the obtained diffraction image (peak of the (622) plane of ITO) and the wavelength λ of the X-ray source, and the lattice distortion ε was calculated based on d. The following formulas (1) and (2) were used for the calculation. TIFF0007638058000001.tif11167
[0102] TIFF0007638058000002.tif11167
[0103] Here, λ is the wavelength (=0.15418 nm) of the X-ray source (Cu Kα radiation), and d0 is the lattice spacing (=0.15241 nm) of ITO in a stress-free state. Note that d0 is a value obtained from the ICDD (The International Centre for Diffraction Data) database.
[0104] The above X-ray diffraction measurement was performed for angles Ψ between the film plane normal and the ITO crystal plane normal of 45°, 50°, 55°, 60°, 65°, 70°, 77°, and 90°, and the lattice strain ε was calculated for each angle Ψ. The angle Ψ between the film plane normal and the ITO crystal plane normal was adjusted by rotating the sample around the TD direction as the rotation axis. The residual stress σ in the ITO film in-plane direction was calculated as sin 2 The relationship between Ψ and lattice strain ε was plotted and the slope of the line was calculated using the following formula (3). TIFF0007638058000003.tif19167
[0105] In the above formula, E is the Young's modulus of ITO (116 GPa), and ν is the Poisson's ratio (0.35). These values are known measured values described in DG Neerinck and TJ Vink, “Depth profiling of thin ITO films by grazing incidence X-ray diffraction”, Thin Solid Films, 278 (1996), pp. 12-17.
[0106] The obtained residual stresses are shown in Table 1. 4) Bending resistance (2-point bending test) The transparent conductive film of each of the Examples and Comparative Examples was cut to a size of 50 mm x 100 mm.
[0107] The cut transparent conductive film was bent from the center of the long side as a starting point, and the distance between two points at which the transparent conductive film broke was measured. The distance between two points is the distance between one end and the other end in the long side direction when the film is bent from the center of the long side as a starting point.
[0108] The results are shown in Table 1.
[0109] [Table 1] [Explanation of symbols]
[0110] 1. Transparent conductive film 2. Glass substrate 3 Transparent conductive layer
Claims
1. A glass substrate and a transparent conductive layer are provided in that order, The thickness of the glass substrate is 50 μm or more and 150 μm or less, the transparent conductive layer is crystalline, the residual stress of the transparent conductive layer is −250.7 MPa or less; A transparent conductive film, characterized in that the surface resistance value of the transparent conductive layer is 1 Ω / □ or more and 30 Ω / □ or less.
2. The transparent conductive film according to claim 1 , wherein the transparent conductive layer contains a metal oxide.
3. 3. The transparent conductive film according to claim 2, wherein the metal oxide is an indium tin composite oxide.
Citation Information
Patent Citations
Transparent conductive film and method for manufacturing the same
JP2012150779A
Surface treatment method for glass film, glass film laminate, and glass film
JP2015063427A
Transparent conductive film and production method thereof
JP2017106124A